A Delayed Post-COVID-19 Silent Thyroiditis - Alkhuboli, Farah; Soukieh, Farah; Subhi, Ahmad; Abusahmin, Hussam (Journal of Diabetes and Endocrine Practice, 2025)
Background Although respiratory symptoms are the predominant manifestations of coronavirus disease 2019 (COVID-19) infection, thyroid dysfunction is a commonly recognized sequela. We report a case of delayed silent thyroiditis that manifested 3 months following COVID-19 infection in a 14-year-old female.Case Description A 14-year-old female presented with palpitations, tremors, and sweating that started around 3 months after the resolution of COVID-19 infection.Her presentation, thyroid function tests, along with ultrasonographic pictures and radioiodine uptake scan of the thyroid were consistent with a diagnosis of silent thyroiditis. She was managed symptomatically with propranolol, after which her symptoms improved, and thyroid function tests returned to normal.Conclusion COVID-19 is a possible trigger for delayed silent thyroiditis that health care providers should recognize for accurate diagnosis and management.
Keywords: COVID-19 infection; thyroiditis; case report